Methods for assessment of the tumour microenvironment and immune interactions in non-small cell lung cancer. A narrative review - Rangamuwa, Kanishka; Aloe, Christian; Christie, Michael; Asselin-Labat, Marie-Liesse; Batey, Daniel; Irving, Lou; John, Thomas; Bozinovski, Steven; Leong, Tracy L.; Steinfort, Daniel (Frontiers in Oncology, 2023)
Non-small cell lung cancer (NSCLC) is one of the leading causes of cancer death worldwide. Immunotherapy with immune checkpoint inhibitors (ICI) has significantly improved outcomes in some patients, however 80-85% of patients receiving immunotherapy develop primary resistance, manifesting as a lack of response to therapy. Of those that do have an initial response, disease progression may occur due to acquired resistance. The make-up of the tumour microenvironment (TME) and the interaction between tumour infiltrating immune cells and cancer cells can have a large impact on the response to immunotherapy. Robust assessment of the TME with accurate and reproducible methods is vital to understanding mechanisms of immunotherapy resistance. In this paper we will review the evidence of several methodologies to assess the TME, including multiplex immunohistochemistry, imaging mass cytometry, flow cytometry, mass cytometry and RNA sequencing.